Algunos razonamientos sobre el aparato formal de la mecánica clásica, relativista y cuántica - Sánchez Ovcharov, Carmen (Revista de Filosofía, 2002)
This article contains the results of our systematization of physics’ quantities and mathematical expressions of the classic, relativistic and quantum mechanics, revealing their common underlying structure. This systematisation was realized ordering some physics’ quantities and mathematical expressions in tables according to their degree of derivation, giving a possibility for a Criterion of Fundamentality for the laws, principles, postulates and equations of each formal apparatus.